The Office Workplace: Communitas and Hierarchical Social Structures - Letkemann, Paul G. (Anthropologica, 2022)
Victor Turner's concept of communitas is being applied to an increasingly diverse number of social situations. Researchers often try to establish the absence of hierarchical or status base structure as a precondition for communitas. The existence of a situational "egalitarianism" is hard to maintain when all social relationships are political. This paper uses excerpts of interviews of civil servants from a small Regional Planning Office in Alberta, Canada. I show the possibility of integrating structural differentiation with the experience of communitas, building on Turner's and related research. This integration helps illustrate the ritual properties in everyday situations, while acknowledging the salience of inherent status and hierarchical distinctions.